Ditch the low flow: Agricultural impacts on flow regimes and consequences for aquatic ecosystem functions. Issue 5 (29th October 2021) - Rideout, Natalie K.; Lapen, David R.; Peters, Daniel L.; Baird, Donald J.
Abstract: Large‐scale, intensive agriculture is a critical activity supporting global food production, yet it has taken a significant toll on the equally critical ecosystem services supplied by global biodiversity. This is particularly true for the planet's most threatened ecosystems: freshwaters. As one of the world's largest agricultural producers, Canada is also home to much of the world's freshwater. As Canada's agricultural capacity expands under climate warming into more northerly latitudes—and in some cases regions with large carbon sinks—it is imperative that this sectoral shift is accompanied by careful management to avoid exacerbating ecosystem service losses. Across Canada, agricultural practices vary in terms of their impact on freshwater ecosystems. Agricultural water extraction, storage behind dams, diversions, dredging and clearing of riparian vegetation can impact more naturalized flow regimes. This review explores the influence of managed low flows on ecosystem functioning in man‐made drainage/irrigation ditch systems. We examine how low flows in these systems can impact ecosystem functions in agricultural watersheds with fragmented natural capital. We provide management options to protect ecosystem functions under a changing climate, recognizing that in agro‐ecosystems, drainage/irrigation ditch systems provide a critical remnant habitat to support biodiversity in otherwise depauperate landscapes.